(untitled) (Revista de História Regional, 2025)
The intrinsic relationship between the countryside and the city is redefined by territorial transformations occurring globally, especially since the late 20th century. The boundaries between these components have become blurred, resulting in spaces that do not belong to either category. In this context, history plays a key role in understanding the current challenges between urban and rural areas, particularly in geographic areas that are strongly influenced by processes belonging to both realities. This article takes the Metropolitan Region of Rosario in Argentina as a case study. This region has been a significant global agro-exporting hub since its origins and continues to play this role today, while also being subject to various urbanization processes. Through a multi-scalar approach, the article presents a descriptive-exploratory historical account of the region’s transformation, aiming to interpret the relationship between the countryside and the city from the origins of the formation of the diverse localities that comprise the region. These localities are mainly linked to agricultural, and livestock uses, articulated with the railway infrastructure process, around which the first urban fabrics of each town developed. The article reflects on the changes over time, culminating in an analysis of contemporary conflicts between these two modes of territorial appropriation.